On generalized derivatives for C1,1 vector optimization problems - Davide La Torre (Journal of Applied Mathematics)
We introduce generalized definitions of Peano and Riemann directional derivatives in order to obtain second-order optimality conditions for vector optimization problems involving C1,1 data. We show that these conditions are stronger than those in literature obtained by means of second-order Clarke subdifferential.